Agriculture, Jobs, and Value Chains in Africa - Christiaensen, Luc (World Bank, Washington, DC, 2020)
This Jobs Solutions Note identifies approaches for development practitioners and policymakers to better integrate poor smallholders into agricultural value chains. Based on curated knowledge and evidence for a specific topic and relevant to jobs, the Jobs Solutions Notes are not intended to be exhaustive; they provide key lessons, solutions and approaches synthesized from the experiences of the World Bank Group and partners. This Note develops a conceptual framework to guide policy choices in using inclusive agricultural value chain development for better job creation in the rural space. As the agricultural iVCD agenda is still nascent and rigorous empirical evidence incipient, it refrains from nuts-and-bolts operational guidance on how to do this.